PERAN WORLD FOOD PROGRAMME (WFP) DALAM MENANGANI KRISIS PANGAN DI HAITI PASCA BADAI MATTHEW (2016-2017) - Silvi Darmawati; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research discusses the role of the World Food Program (WFP) in dealing with the food crisis in Haiti after hurricane Matthew 2016-2017. The purpose of this study is to identify and explain the role of the World Food Program (WFP) in dealing with the food crisis in Haiti after hurricane Matthew. Consecutive natural disasters and low income are the background of the food crisis in Haiti. In dealing with these problems, the government of Haiti needs help from outside to restore the state of the country, especially in dealing with food problems due to the difficulty of people getting and accessing food. For this reason, WFP as an international organization in the field of food intervenes to solve the problem of hunger in Haiti. This research is a qualitative research, which is explained based on the facts at the level of group behavior analysis. The author uses the theory of international organizations in the concept of food security by using a pluralism perspective. To discuss this issue, the authors collected data from books, journals, websites, data reports from WFP, regarding the role of WFP in dealing with the food crisis in Haiti after hurricane Matthew in 2016-2017. The findings of this study indicate that WFP implements several programs in dealing with problems in Haiti, namely Emergency Operations (EMOP), Relief and Rehabilitation Operations (PRRO), Development Operations (DEV), and Special Operation (SO). In overcoming the food crisis in Haiti, WFP acts as an instrument by creating and implementing its programs, acting as an arena or forum by opening open donations as a forum for other actors who want to help Haiti deal with the food crisis, and WFP acts as an actor that is, WFP can freely request, obtain and cooperate with other international organizations and several countries without coercion and the interest of power. Keyword: Role, International Organization, WFP, Haiti, Hurricane Matthew, Food Insecurity